Internet addiction in a student of nursing - Kuljić Miljana; Kulić Veselinka; Kulić Ljiljana; Mijović Biljana; Živanović Srđan (Association of Nurses Technicians and Midwives, 2019)
INTRODUCTION: Internet addiction is a topic that is widely debated in scientific circles and the media. Students spend a lot of time in content-related activities online, neglecting common activities such as socializing, business obligations, learning, home affairs, etc., and have difficulty interrupting internet activities, even when they themselves recognize it is time for it. AIM: The aim of this research was to investigate Internet addiction among students of the Medical Care, Faculty of Medicine in Foča. MATERIAL AND METHODS: The research was conducted at the Medical Faculty in Foča in the period from 07.11. until 09.11.2016. year with health care students. The selected study design is a cross section study. The study covered 60 students, the first, second and third year of studies that were present on the days of the study and volunteered to participate in the research. RESULTS: The survey involved 60 respondents, of whom 21 are men (35%) and 39 women (65%), ages 18 to 24 years old. All of our respondents are Internet users. The largest percentage of respondents (66.7%) use the internet for 2 to 4 hours. The largest number of respondents first accessed the Internet at the age of 13 (21.7%). Most respondents use Facebook as a social network 56 (93.3%), while the least number of Twitter users. CONCLUSION: All of our respondents are Internet users, and the largest percentage of respondents (66.7%) use the internet for 2 to 4 hours. The largest number of respondents first accessed the Internet at the age of 13 (21.7%).